Molecular phylogeny of Diphtherophora de Man, 1880 (Nematoda: Diphtherophoridae), with description of a new species - Ghaderi, Reza; Hesar, Abas Mokaram; Karegar, Akbar; Pereira, Tiago José (Zootaxa, 2020)
The poorly-known nematodes of the genus Diphtherophora are soil inhabitants often found in the vicinity of plant roots. In the present study, we characterize a new species belonging to the genus Diphtherophora, named D. eldarica n. sp., from Iran using both morphological and molecular approaches. The new species is characterized by striated cuticle at the anterior end of the body, head offset from the body contour, spear 15–17 µm in length, rod-shaped sperm, overhanging cuticle on the anterior lip of the anus, and a conical tail bent dorsally near the terminus. Diphterophora eldarica n. sp. also lacks ventromedian neck papillae whereas male specimens bear two precloacal ventromedian supplements at the level of the spicules. Additionally, we provide morphological and molecular data for four known Diphtherophora species including D. geraerti, D. caudata, D. perplexans, and D. tenera collected from soils of different plants and localities in Iran. Using the D2–D3 expansion segments of the 28S ribosomal (rRNA) gene including D. eldarica n. sp. and additional known species from Iran, we explore for the first time species relationships in the genus Diphtherophora within a molecular phylogenetic framework. Our results support: 1) the monophyly of the genus Diphtherophora with respect to the outgroup taxa (Tylolaimophorus and representatives of Trichodoridae), 2) the existence of six strongly supported clades within Diphtherophora, and 3) a sister relationship between D. eldarica n. sp. and a clade formed by D. perplexans and Diphtherophora sp. from the USA. Finally, this study emphasizes the diversity of the genus Diphtherophora in Iran.